2020
DOI: 10.1111/jfpp.14665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron‐beam irradiation on postharvest strawberry quality

Abstract: To safeguard the ecosystem and facilitate the international trade of fresh agricultural products, phytosanitary treatments, particularly newly emerged electron‐beam (e‐beam) irradiation, are recommended because they are eco‐friendly and do not adversely affect postharvest preservation. However, the effects of this technique on “Maehyang” strawberries are unknown. Therefore, herein, the effects of e‐beam irradiation (≤1 kGy) on postharvest preservation of strawberry during storage were evaluated. E‐beam irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…These results showed that Psychrophile and Pseudomonas grew faster and were the dominant populations in PE, PBAT/PBS and PBAT/PCL treatments. It could inhibit the fruit decay by killing spoilage microorganisms inhabiting the tissues or fruit skin (Yoon et al., 2020). Therefore, combined with the data of decay rate, it can be concluded that Psychrophile and Pseudomonas were the dominant spoilage bacteria of A. mongolicum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that Psychrophile and Pseudomonas grew faster and were the dominant populations in PE, PBAT/PBS and PBAT/PCL treatments. It could inhibit the fruit decay by killing spoilage microorganisms inhabiting the tissues or fruit skin (Yoon et al., 2020). Therefore, combined with the data of decay rate, it can be concluded that Psychrophile and Pseudomonas were the dominant spoilage bacteria of A. mongolicum .…”
Section: Resultsmentioning
confidence: 99%
“…In (Yoon et al, 2020). Therefore, combined with the data of decay rate, it can be concluded that Psychrophile and Pseudomonas were the dominant spoilage bacteria of A. mongolicum.…”
Section: Microbiological Populationmentioning
confidence: 87%
“…With blueberries, the use of e-beam irradiation at doses below 3 kGy has demonstrated to be a gentle processing that does not affect monomeric anthocyanin and antioxidant activity [ 93 ]. Protection of anthocyanins, color, phenols and antioxidant activity has also been observed in strawberries processed at 1 kGy [ 94 ].…”
Section: Effect Of E-beam Irradiation In the Extraction Of Anthocyaninsmentioning
confidence: 99%
“…The raspberry samples were taken periodically during storage for analysis immediately after treatment: T0, 7 days (T7) and 14 days (T14) after e-beam irradiation. The pH of raspberry samples was measured with a digital pH meter (KDD002) as described by Yoon et al (2020). The TA was determined via titration with 0.1 N NaOH to an end of pH 8.2 and expressed as a percentage of citric acid (Han et al, 2004).…”
Section: Physicochemical Analysismentioning
confidence: 99%